DNA methyltransferase 1 mediated aberrant methylation and silencing of SHP-1 gene in chronic myelogenous leukemia cells. (July 2017) - Li, Yinghua; Liu, Xuedong; Guo, Xiufeng; Liu, Xiao; Luo, Jianmin
Highlights: We investigated the mechanism of epigenetic silencing of SHP-1 in CML. The 22 CpG sites located in SHP-1 promoter is aberrantly methylated in K562 cells. DNMT1 silencing induced the demethylation of SHP-1 promoter and SHP-1 overexpression. We uncovered the underlying mechanism of SHP-1 in CML. Abstract: Introduction: Extensive studies on SHP-1 protein and SHP-1 mRNA revealed that the diminishment or abolishment of the expression of SHP-1 in leukemias/lymphomas was due to aberrant promoter methylation. Thus far, the mechanism of epigenetic silencing of the SHP-1 tyrosine phosphatase gene that occurs in chronic myelogenous leukemia cells remains poorly understood. Methods: The expressions of the target molecules were determined by quantitative real time PCR and western blot, respectively. Bisulfite sequencing PCR was used to detect methylation status of DNA CpG. The lentiviral vectors were applied to modify gene expression. Results: In the present study, we found that the promoter 2 of SHP-1 gene is located between positions from −577 bp to +300 bp, and 22 CpG sites contained in positions −353 bp ∼ +182 bp are aberrantly methylated in K562 cells. In vitro, we demonstrated that DNMT1 silencing induced demethylation of the 22 CpG sites located in the SHP-1 promoter and re-expression of SHP-1 gene in K562 cells. Moreover, we proved that the expression levels of DNMT1 and SHP-1 mRNA and protein were negatively correlated in K562 cells and BM aspirates mononuclear cells from CML patients. Conclusion: Collectively, these results indicate that DNMT1 mediates aberrant methylation and silencing of SHP-1 gene in chronic myelogenous leukemia cells, and provide a novel therapeutic target for CML.